2022
DOI: 10.1111/medu.14867
|View full text |Cite
|
Sign up to set email alerts
|

Building a theoretical model for virtual interprofessional education

Abstract: Background: Virtual interprofessional education (IPE) has emerged as a promising alternative to traditional in-person IPE. However, theoretical frameworks to support virtual interprofessional learning are not well established. Two theoretical frameworks emerged as relevant to virtual IPE: (1) the Canadian Interprofessional Health Collaborative (CIHC) interprofessional learning framework and (2) Dornan's Experience-Based Learning Model (ExBL) of workplace learning. In this study, we sought to explore virtual IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
(118 reference statements)
0
9
0
Order By: Relevance
“…However, the COVID‐19 pandemic prevented in‐person delivery of this course and motivated the development of a virtual alternative. Previous studies have shown the virtual environment allows for the acquisition of communication and role clarification competencies, in an environment less burdened by professional hierarchies 8 . Virtual learning has also been shown to yield positive results in the teaching of anatomy, as demonstrated by improved academic performance and positive qualitative feedback from students.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the COVID‐19 pandemic prevented in‐person delivery of this course and motivated the development of a virtual alternative. Previous studies have shown the virtual environment allows for the acquisition of communication and role clarification competencies, in an environment less burdened by professional hierarchies 8 . Virtual learning has also been shown to yield positive results in the teaching of anatomy, as demonstrated by improved academic performance and positive qualitative feedback from students.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown the virtual environment allows for the acquisition of communication and role clarification competencies, in an environment less burdened by professional hierarchies. 8 Virtual learning has also been shown to yield positive results in the teaching of anatomy, as demonstrated by improved academic performance and positive qualitative feedback from students. This approach offers advantages such as the ability to isolate and appreciate anatomical structures, time-efficiency, and the opportunity to visualize structures multiple times.…”
Section: Introductionmentioning
confidence: 99%
“…3 Building a foundation of diverse and inclusive student and graduate cohorts requires schools to own and drive the necessary change from within. 1,4,5 Students should not have to shoulder the burden of change, nor should they be responsible for continued action to raise and address systemic power imbalances inherent within the structure of medical academies. Foreshew and Al-Jawad note the important role of medical institutions in decolonisation and proposes that reflection and observation must urgently move to informed and committed action because:…”
Section: Orcidmentioning
confidence: 99%
“…1 , 2 In the last 2 years, the COVID‐19 pandemic has boosted the use of ‘virtual’ IPE training; however, its theoretical groundworks are still lacking. 3 In their paper ‘Building a Theoretical Model for Virtual IPE,’ Azim et al 4 explored the extension of two interprofessional and workplace learning frameworks into the virtual setting using simulation‐based workshops in which both medical and nursing students participated. Without the context of the clinical workplace and professional labels, the authors found that students participated more freely.…”
mentioning
confidence: 99%
See 1 more Smart Citation